Manihot macrocarpa (Euphorbiaceae), an unusual rain forest species from Brazil - Martins, Márcio Lacerda Lopes; Carvalho, Paulo Cezar Lemos De; Ledo, Carlos Alberto Da Silva; Amorim, André Márcio (Phytotaxa, 2017)
Manihot macrocarpa is described and illustrated. This species resembles M. compositifolia because of its lianescent habit and indehiscent fruits, but differs by its simple, unlobed leaves and orbicular fruits (vs. compound, [3–]5[–7]-foliolate leaves and ellipsoid fruits in M. compositifolia). Manihot macrocarpa occurs in areas of rain forest in southern Bahia State. It is considered endangered (EN B1) because it has an extent of occurrence smaller than 5,000 km2 and is known from no more than five locations. A key to Manihot species with indehiscent fruits and comments about the new species are provided.